Medical Personnel in the Context of Informatization - Yu. Yu. Snegireva; N. Sh. Sarkhadov; E. K. Smirnova (Здоровье мегаполиса)
Background. The relevance of the chosen topic is due to the rapid development of information technologies in healthcare. The article discusses the key aspects of introduction of digital technologies into healthcare and training of medical staff.Purpose. To investigate the impact of digitalization on healthcare, identify key problems and difficulties associated with the adaptation of healthcare workers to new technologies, and develop recommendations for improving the digital competence in medical personnel in order to successfully integrate information technology into clinical practice.Materials and methods. An integrated approach, including the analysis of scientific literature, regulations, and reports on digitalization in healthcare, was applied. Also, the authors used the results of sociological survey among 419 healthcare workers from Moscow state healthcare organizations.Results. The survey showed that 65% of respondents have a positive attitude towards digitalization, but 42% identified insufficient technical support as the main difficulty. The results also point to the need to improve educational programs in order to make use of new technologies more efficient. The importance of an integrated approach to medical education, including advanced training courses and practical trainings, is emphasized. Successful digitalization of healthcare depends on the readiness of medical personnel to adapt to changes, which should improve the quality and accessibility of medical services.